'Wounded religious masculinities': Muslim men's opposition against male circumcision in Turkey. (15th March 2023) - Barutçu, Atilla
ABSTRACT: Male circumcision maintains a strong connection with religious responsibilities and masculinity construction in Turkey, but some Muslim men oppose this ritual today. This paper argues that opposing approaches to male circumcision on religious grounds do not necessarily enable a critical view of masculinity in general. Muslim men's opposition against male circumcision shows four interdependent approaches about the juxtaposition of male circumcision, religion, and masculinity: (1) 'Defending anti-circumcision' as an example of practicing religion correctly, (2) 'practicing religion correctly' as a necessity for piety, (3) 'piety' as a requirement for masculinity, and (4) hence defending anti-circumcision as an obligation for 'masculinity.' The fourth point takes us back to the first one, and this creates a cycle which also shows how these men construct their own masculinity. The study shows that being circumcised and uncircumcised can both be positioned as a strategy that supports masculinity and internal hegemony in the same geography.